Analysis of influencing factors of anxiety and depression in maintenance hemodialysis patients and its correlation with BDNF, NT-3 and 5-HT levels - Peng,Xiaoyan; Feng,Sujuan; Zhang,Poxuan; Sang,Shengmei; Zhang,Yi (PeerJ, 2023)
Objective The aim of this study is to examine the factors that contribute to anxiety and depression in individuals undergoing maintenance hemodialysis (MHD), as well as their association with serum levels of brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), and serotonin (5-HT). Methods In May 2020 and June 2022, 120 MHD patients who received MDH treatment at our hospital were enrolled. The control group was composed of 60 healthy adults (>18) who completed the physical examination at the same time. The serum levels of BDNF, NT-3, and 5-HT in patients and clinical data of MHD patients with different degrees of anxiety and depression were compared. The Pearson correlation was used to evaluate the correlation between anxiety and depression scores and serum BDNF, NT-3,5-HT levels in patients with MHD. Multivariate analysis was employed to analyze the risk factors of anxiety and depression in MHD patients. Results The incidence of anxiety and depression in 120 MHD patients was 34.17% (41/120) and 64.17% (77/120), respectively. The levels of serum NT-3 and 5-HT in the anxiety group were higher than those in the non-anxiety and control group, and the levels of serum NT-3 in the non-anxiety group were higher than those in the control group (P < 0.05). The levels of serum BDNF, NT-3 and 5-HT in the depressed group were higher than those in the non-depressed group and control group, and the levels of serum NT-3 in the non-depressed group were higher than those in the control group (P < 0.05). SAS score was positively correlated with serum NT-3 and 5-HT levels, while the SDS score was negatively correlated with serum BDNF and positively correlated with serum NT-3 and 5-HT levels. Female, rural household registration, and restless leg syndrome were independent risk variables for anxiety in patients with MHD (P < 0.05). Rural household registration, economic deterioration, fatigue, insomnia, and vascular pain were independent variables of depression risk in patients with MHD. Conclusion Anxiety and depression in patients with MHD are closely related to the levels of serum BDNF, NT-3, and 5-HT. Female, rural household registration, more than eight dialysis times/month, insomnia, and restless leg syndrome are the risk factors for anxiety in patients with MHD. Rural household registration, economic deterioration, fatigue, insomnia, and vascular pain are the risk factors for depression in patients with MHD. The clinical implication of these findings suggests that these indexes may perhaps serve as biological indicators of anxiety and depression amongst patients undergoing MHD. Such investigation can hence contribute to early detection, monitoring, and potentially enable the depiction of novel therapeutic strategies for managing these adverse states.
Keywords: Maintenance hemodialysis; Anxiety; Depression; Influencing factors; BDNF; NT-3; 5-HT